_ PENDAFTARAN TANAH SISTEMATIS LENGKAP DI DESA LINGGASANA KECAMATAN CILIMUS KABUPATEN KUNINGAN: _ - Mila Listiya Dewi; Meta Indah Budhianti (Faculty of Law, Universitas Trisakti, 2023)
Kuningan is targeted in PTSL zone. In 2021, The Kuningan District Land Office has set a goal of 70,000 fields for PTSL. The issue is whether land registration through the PTSL program already implemented in Linggasana Village, Cilimus District, Kuningan Regency based on the ATR/Ka.BPN Ministerial Regulation No. 6 of 2018 about PTSL, and what the challenges in implementation. The type of research is descriptive analytic study, normative law is applied, and secondary data is the sort of data used. The research result is analyzed by qualitative and examined by a deductive perspective. As a research and observation result, it has been determined that Linggasana Village's PTSL implementation is experiencing obstacles due to some of people did not want to participate in PTSL. The conclusion is the PTSL Program in Linggasana Village, Cilimus District, Kuningan Regency still has obstacles and it is decrease the performance of the land office in implementing the PTSL Program.